Characterization of biosurfactant from yeast using residual soybean oil under acidic conditions and their use in metal removal processes - Camargo, Franciele Pereira; de Menezes, Aparecido Juńior; Tonello, Paulo Sérgio [UNESP]; Dos Santos, André Cordeiro Alves; Duarte, Iolanda Cristina Silveira (Oxford University Press (OUP), 2018)
This study aimed at the production of biosurfactants from yeasts under acidic conditions using residual soybean oil as a carbon source, as well as the biosurfactant produced in the solubilization of metals in sewage sludge. The yeast Meyerozyma guilliermondii was considered the best producer in both pH 4.0 and 2.0; therefore, the product obtained by this yeast was characterized by Fourier transform infrared (FT-IR) and 1H nuclear magnetic resonance (NMR) spectroscopy. Moreover, it was applied in metal removal assays in anaerobic sewage sludge. The spectra obtained in FT-IR suggested that M. guilliermondii's biosurfactant had a similar structure to glycolipids from the sophorolipid class, and it was confirmed by 1H NMR spectroscopy. In the bioleaching assays, the application of biosurfactant (2%) produced by M. guilliermondii with pH adjusted to 2.0 was able to solubilize 15.9% of cadmium from the sewage sludge.
Keywords: Anionic biosurfactant; Bioleaching; Bioremediation; Glycolipid; Low-cost substrate; Sophorolipid